A common modular design of nervous systems originating in soft-bodied invertebrates - Gribkova, Ekaterina D.; Lee, Colin A.; Brown, Jeffrey W.; Cui, Jilai; Liu, Yichen; Norekian, Tigran; Gillette, Rhanor (Frontiers in Physiology, 2023)
Nervous systems of vertebrates and invertebrates show a common modular theme in the flow of information for cost-benefit decisions. Sensory inputs are incentivized by integrating stimulus qualities with motivation and memory to affect appetitive state, a system of homeostatic drives, and labelled for directionality. Appetitive state determines action responses from a repertory of possibles and transmits the decision to a premotor system that frames the selected action in motor arousal and appropriate postural and locomotion commands. These commands are then sent to the primary motor pattern generators controlling the motorneurons, with feedback at each stage. In the vertebrates, these stages are mediated by forebrain pallial derivatives for incentive and directionality (olfactory bulb, cerebral cortex, pallial amygdala, etc.) interacting with hypothalamus (homeostasis, motivation, and reward) for action selection in the forebrain basal ganglia, the mid/hindbrain reticular formation as a premotor translator for posture, locomotion, and arousal state, and the spinal cord and cranial nuclei as primary motor pattern generators.Gastropods, like the predatory sea slug Pleurobranchaea californica, show a similar organization but with differences that suggest how complex brains evolved from an ancestral soft-bodied bilaterian along with segmentation, jointed skeletons, and complex exteroceptors.Their premotor feeding network combines functions of hypothalamus and basal ganglia for homeostasis, motivation, presumed reward, and action selection for stimulus approach or avoidance. In Pleurobranchaea, the premotor analogy to the vertebrate reticular formation is the bilateral "A-cluster" of cerebral ganglion neurons that controls posture, locomotion, and serotonergic motor arousal. The A-cluster transmits motor commands to the pedal ganglia analogs of the spinal cord, for primary patterned motor output. Apparent pallial precursors are not immediately evident in Pleurobranchaea's central nervous system, but a notable candidate is a subepithelial nerve net in the peripheral head region that integrates chemotactile stimuli for incentive and directionality. Evolutionary centralization of its computational functions may have led to the olfaction-derived pallial forebrain in the ancestor's vertebrate descendants and their analogs in arthropods and annelids.